EFFORTS TO IMPROVE KNOWLEDGE IN IMPLEMENTING CLEAN AND HEALTHY LIVING AMONG ELEMENTARY SCHOOL CHILDREN - kusyani, Asri; Vidhiastutik , Yusiana (Community Service Journal of Indonesia, 2025)
Clean and Healthy Living Behavior (PHBS) is a reflection of a family lifestyle that always pays attention to and maintains the health of all family members, including elementary schools . Effort promotional And preventive through giving education health expected able to increase the understanding of elementary school children to behave in a clean and healthy way. Improving Understanding in Elementary School Children Elementary school students' knowledge related to behaving in a clean and healthy way The method of increasing knowledge in preventing diseases in children such as diarrhea is carried out by providing health education through Power media. Point And leaflet to 40 student class V SDN in Peterongan. Implementation All over student given questionnaire pre-test and post-test for evaluate effectiveness education health to knowledge. Counseling health conducted on October 25, 2025. The results of the Wilcoxon Signed Rank Test showed a significant value (p<0,000) which indicates that health education has a significant effect on increasing knowledge clean and healthy living behavior. Education health proven effective in increase and equalize the level of knowledge of school children in behaving in a clean and healthy way, providing education can provide understanding to elementary school children. Good understanding has an impact on clean and healthy behavior to improve the health level of students.